Polycystic ovary syndrome and risk of stillbirth: a nationwide register‐based study. (20th September 2021) - Valgeirsdottir, H; Kunovac Kallak, T; Sundström Poromaa, I; Jonsson, M; Roos, N; Lindström, L; Wikström, A‐K
Abstract : Objective: To investigate whether polycystic ovary syndrome (PCOS) is associated with increased risk of stillbirth and whether any such association is linked to PCOS with a severe hyperandrogenic profile. Design: Nationwide register‐based cohort study. Setting: Sweden. Population: The cohort consisted of women giving birth to singleton infants in 1997–2015. All women with a diagnosis of PCOS in the period 1997–2017 and a randomly selected reference group of women without PCOS diagnosis were included. PCOS with a severe hyperandrogenic profile was defined as a PCOS diagnosis with at least two dispensations of prescribed anti‐androgens during 2005–2017. Methods: The risk of stillbirth in women with PCOS was estimated through multiple logistic regression, using women without PCOS as a reference. Risks were expressed as adjusted odds ratios (aORs) with 95% confidence intervals (95% CIs), adjusted for maternal age, parity, body mass index, type‐1 diabetes, educational level and country of birth. Main outcome measures: Stillbirth, at ≥22 weeks of gestation in 2008–2015 and at ≥28 weeks of gestation in 1997–2007. Results: Compared with women without PCOS ( n  = 241 750), women with PCOS ( n  = 41 851) had a 50% increased risk of stillbirth (aOR 1.50, 95% CI 1.28–1.77). The incidence of stillbirth in women with PCOS was particularly increased at term. Women with PCOS and a severe hyperandrogenic profile ( n  = 13 713) did not have a stronger association with stillbirth than women with PCOS who did not have such a profile. Conclusions: PCOS is associated with stillbirth and should be considered as a possible risk factor in antenatal care. Further research is warranted to investigate possible causal mechanisms. Tweetable abstract: Women with PCOS have increased risk of stillbirth, and the incidence is particularly increased at term. Tweetable abstract: Women with PCOS have increased risk of stillbirth, and the incidence is particularly increased at term.